Academic Success - Hargreaves, Wendy; Bartlett, Cristy; Derrington, Kate (Open textbook library., 2021)
Academic Success is designed to help students on their university journey. It is divided into four parts, each reflecting different aspects of a student’s tertiary experience. Part A: Successful Beginnings addresses what it is like to be a new student at an Australian university. Part B: Successful Foundations introduces basic skills in English language, techniques for accessing and working with information, and understanding academic integrity. Part C: Successful Study Skills presents the everyday, core skills that successful students use while at university. Lastly, Part D: Successful Assessment meets head-on the challenges of tertiary assessments. This open book ultimately aids students across all disciplines in achieving academic success at university.